Motivasi Pengunjung Perpustakaan Soeman HS Pekanbaru Provinsi Riau - Atikah Ulayya (Universitas Muhammadiyah Sumatera Utara, 2022)
Soeman HS Library claimed is the best library in ASEAN. This library even became one of the landmarks in Pekanbaru City which has the capacity to accommodate 1000 visitors. Visitors who come to the library have various purposes. Some of them come to read, do their assignments, lend books, and use the facilities in the library. The number of visitors coming here fluctuates every year, because they do not come to the library every day. This study aims to determine the visitors motivation coming to Soeman HS Library and to analyze the factors that influence the visitors motivation to visit Soeman HS Library. The method used for this study was quantitative descriptive research. Primary data were obtained directly through a questionnaire and secondary data were obtained from Soeman HS Library Service Section. The sampling method used was quota sampling technique with 100 respondents who are visitors to Soeman HS Library. The results of this study indicated that the motivation of visitors to visit the HS Soeman Library was quite high, for about 81.1% for First to Third Floors, and 80.0% for the Ground Floor (Particularly for Children Services). There was a relationship between some factors that influence the visitors to visit the library, such as the desires and needs, library services as well as facilities and infrastructure